The mind and method of the legal academic - Smits, J.M. (Cheltenham, UK : Edward Elgar, 2012)
'In a context of changing times and current debate, this highly topical book discusses the aims, methods and organization of legal scholarship. Jan Smits assesses the recent turn away from doctrinal research towards a more empirical and theoretical way of legal investigation and offers a fresh perspective on what it is that legal academics should deal with and how they should do it. The book also considers the consequences which follow for the organization of the legal discipline by universities and uses this context to discuss the key questions of the internationalization of law schools, quality assessments, legal education and the research culture. Being the first book to address the aim and goals of legal scholarship in an international context, this insightful study will appeal to academics, graduate students, researchers and policymakers in higher education'--Provided by publisher.
Legal science : a typology -- The Homo juridicus : towards a redefinition of normative legal science -- Methodology of normative legal science -- Organization of the legal-academic discourse.
Includes bibliographical references (pages 152-173) and index.
Keywords: Law -- study and teaching; Learning and scholarship